Entrepreneurship - Greene, Cynthia L. (Mason, OH : South-Western Cengage Learning, 2011)
The design and content of each Learner Guide in the 21st Century Business Series is engaging yet easy for students to use. The content focuses on providing opportunities for applying 21st century skills while enabling innovative learning methods that integrate the use of supportive technology and creative problem-solving approaches in today's business world
Includes index
BSBA
Keywords: Entrepreneurship